Tumor-Like Reaction to Polypropylene Mesh from a Mid-Urethral Sling Material Resembling Giant Cell Tumor of Vagina. (18th December 2017) - Azadi, Ali; Bradley, James A.; O'Connor, Dennis M.; Azadi, Amir; Ostergard, Donald R.
Abstract : Background . Polypropylene material is widely used in gynecological surgery. There are few reports regarding its carcinogenic potential. There is lack of evidence supporting tumor formation directly attributed to the use of polypropylene material. Case . This patient is a 49-year-old woman with a history of stress urinary incontinence which required a MiniArc® Sling who presented with a hard, tender, immobile mass on the anterior vaginal wall. Pathological analysis of the mass revealed a tumor-like reaction to the polypropylene material that resembled a giant cell tumor of soft tissue. Conclusion . The use of polypropylene in surgery is ubiquitous across disciplines; thus consideration for a tumor-like reaction to the material should exist for patients who present with a mass near the surgical site.